Trichoneura peruviana (Poaceae, Trichoneurinae), a new species from Peru - Gutiérrez, Harol; Castañeda, Roxana; Montesinos-Tubée, Daniel B.; López, Jorge; Gonzales, Teresa; Norabuena M., Edgar; Sotelo M., Alejandrina (Phytotaxa, 2020)
Trichoneura peruviana sp. nov. is described and illustrated. The new species, from the Western Cordillera de los Andes in Peru, in the middle of the snowy Goylanto and Paylogen at Omate valley, differs from T. lindleyana in having longer glumes (lower glumes 5–5.25 × 0.2–0.25 mm and upper glumes 5.5–5.7 × 0.3–0.4 mm), shorter fertile lemmas 2.1–2.5 mm long with ciliate margins, the cilia 0.5–0.6 mm long, and the lemma apex is dentate, 2−fid, and 1-awned with awns 1.5−3.5 mm long. A key to the species of Trichoneura in Peru is included and the conservation status of the new species is evaluated.